Complicated Amyand’s Hernia in a Neonate - Mandhan, Parkash; Al Rayes, Talal; Ali, Mansour J; Aldhaheri, Mahmoud (Journal of Neonatal Surgery, 2014)
Amyand’s hernia is a rare clinical entity in which the vermiform appendix is present within the inguinal hernia sac. Here, we report a 5-day-old neonate with dysmorphic features referred to us with a tender irreducible right inguino-scrotal swelling. Surgical exploration showed gangrenous appendix with a peri-appendicular abscess in the inguinal hernia sac. Appendectomy and right herniotomy was performed.